2002
DOI: 10.1089/089277902761403041
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Laparoscopy-Assisted Placement of Tenckhoff Catheters: An Improved Technique to Facilitate Peritoneal Dialysis

Abstract: The MLA technique of dialysis catheter placement appears to have similar or greater efficacy than the open technique. It is a viable teaching procedure, and with reusable 3-mm ports and shorter operative times, it is cost efficient as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 7 publications
1
24
1
Order By: Relevance
“…Unlike most previous studies [22,25,27,28] with the exception of that by Wright et al [23], in this study, postoperative pain and the requirement of analgesics did not differ between the laparoscopic and open groups. A likely explanation is that the pain caused by a limited dissection via mini wound in the open group was equivalent to the mild pain produced by carbon dioxide pneumoperitoneum during the laparoscopic procedure [31].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Unlike most previous studies [22,25,27,28] with the exception of that by Wright et al [23], in this study, postoperative pain and the requirement of analgesics did not differ between the laparoscopic and open groups. A likely explanation is that the pain caused by a limited dissection via mini wound in the open group was equivalent to the mild pain produced by carbon dioxide pneumoperitoneum during the laparoscopic procedure [31].…”
Section: Discussioncontrasting
confidence: 87%
“…Early and late complications did not statistically differ in the present study. Similar results were also shown in previous comparative studies [22,23,25], although others have reported reduced outflow obstruction when using laparoscopy [26][27][28][29]. One portsite bleeding was noticed by Draganic et al in thirty laparoscopic placements [22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Omentopexy requires a suture passing needle such as Endoclose TM (Covidian, Norwalk, CT), Carter-Thompson device or laparoscopic suturing equipment and nonabsorbable suture. Mini-laparoscopic instruments have also been used with equal success [95,127,[141][142][143]. Despite the paucity of publications comparing leak rates and the size of trocars, most authors recommend the smallest ports available in a non-cutting variety to allow the quickest healing of the peritoneum, thus facilitating early start of PD and low leak rate.…”
Section: Surgical Techniquementioning
confidence: 99%